2019
DOI: 10.1080/23312521.2019.1698387
|View full text |Cite
|
Sign up to set email alerts
|

“Oh God! Why Did You Let Me Have This Disability?”: Religion, Spirituality and Disability in Three African countries

Abstract: Oh God! Why did you let me have this disability?': religion, spirituality and disability in three African countries BackgroundReligion and spirituality are some of the central philosophies in coping with disability (Claasens, Shaikh, Swartz 2018). Spirituality is a broader term and may be viewed as an umbrella concept under which one finds religion; the latter is concerned with public participation in a faith community with specific practices and doctrines (Walker, 1992). Phillips (2003) as cited by Marin & Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Being in a church provides an environment where the children feel accepted and included. Given that children also reported that being able to go to church was a facilitator for participation, intervention programmes should also consider embedding activities linked to religious activities, particularly for children from countries where religion is more prevalent (Mugeere et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Being in a church provides an environment where the children feel accepted and included. Given that children also reported that being able to go to church was a facilitator for participation, intervention programmes should also consider embedding activities linked to religious activities, particularly for children from countries where religion is more prevalent (Mugeere et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a shift of advocacy for persons with ID by raising awareness in communities and increasing access to education for and employment of persons with ID to reduce negative attitudes and beliefs regarding ID. In addition, religion other than traditional beliefs can be helpful for people with ID in keeping a strong mindset and making them feel accepted (Mugeere et al, 2020). For example, the church gives people with ID and their families emotional, social, and economic support, e.g., providing jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these latter authors term these findings as “unique spiritual and religious profiles” and suggest that it is important to understand “which spiritual and religious dimensions are disproportionately more likely to exist among a given population with a particular disability” ( Hodge & Reynolds 2019 :75). Similarly, people with physical disabilities are more likely to find comfort from faith that helps them face their challenges ( Mugeere et al 2020 ). While there is little information about spirituality from the perspective of those with intellectual disability, interviews with adults with autism who were non-verbal (using assistive communication technology) revealed a great sensitivity towards their personal spirituality, including strong evidence of transcendental experiences that provided support and hope to individuals ( Hills et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%